1991
DOI: 10.1093/bja/66.5.617
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Complications Following the Use of Continuous Extradural Analgesia With Bupivacaine

Abstract: We describe a patient in whom continuous extradural analgesia with bupivacaine resulted in toxic plasma concentrations causing severe cerebral irritation. We discuss recent studies using continuous extradural bupivacaine, reports of toxicity and comment on the importance of monitoring drug concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Bupivacaine, an amide-type local anesthetic, is one of the most widely used local anesthetics for surgical anesthesia and pain management. Previous studies have reported that bupivacaine might be neurotoxic and even clinically recommended dose of bupivacaine also can cause severe neurological complications, which brings extra medical and economic burden to the patients and their families [1][2][3]. However, the exact mechanism underlying the neurotoxicity of bupivacaine is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Bupivacaine, an amide-type local anesthetic, is one of the most widely used local anesthetics for surgical anesthesia and pain management. Previous studies have reported that bupivacaine might be neurotoxic and even clinically recommended dose of bupivacaine also can cause severe neurological complications, which brings extra medical and economic burden to the patients and their families [1][2][3]. However, the exact mechanism underlying the neurotoxicity of bupivacaine is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Lignocaine levels can be assessed in most hospital laboratories allowing titration of continuous epidural infusions (Tobin et al 1993). The toxicity of local anaesthetics requires the monitoring of plasma drug concentration to predict unwanted reactions (Dunne & Kox, 1991).…”
Section: Evidence Of Neurological Damagementioning
confidence: 99%